Appraisal And Speech Structure Of Contestants’ Speeches In Speech Contest Of ESA WEEK Competition - Ghasani, Betari Irma; Sofwan, Ahmad (Universitas Negeri Semarang, 2017)
Performing a persuasion speech and delivering meanings through spoken text poses many challenges for students. As a part of interpersonal meanings, appraisal helps the speaker expressing their position in speech through the choice of words or diction. The chosen diction enables the speaker to precisely realize the message she/he intends to convey through spoken text. Furthermore, in order to guide the listener so they can understand of speaker’s ideas, a clear speech structure is needed. Integrating the theories of appraisal (Martin and White, 2005) and speech structure (Sellnow, 2005), this thesis was intended to explain the appraisal and the speech structure on the students’ speeches in speech contest of ESA WEEK Competition. By using Discourse Analysis (Bavelas, 2002; Celce-Murcia and Olshtain, 2007), the data – in the form of transcripts from video recordings – were analyzed. The findings map out the high use of appreciation of attitude, entertain of engagement, and focus of graduation applied. Those appraisal, moreover, were highly found in the body of the speech. Finally, this thesis provides suggestions that teaching the speech structure and how to convince the listener by using appraisal is needed for better speeches.